Highly variable penetrance of abnormal phenotypes in embryonic lethal knockout mice [version 2; referees: 1 approved, 2 approved with reservations] - Robert Wilson (Wellcome Open Research, 2017)
Background: Identifying genes that are essential for mouse embryonic development and survival through term is a powerful and unbiased way to discover possible genetic determinants of human developmental disorders. Characterising the changes in mouse embryos that result from ablation of lethal genes is a necessary first step towards uncovering their role in normal embryonic development and establishing any correlates amongst human congenital abnormalities. Methods: Here we present results gathered to date in the Deciphering the Mechanisms of Developmental Disorders (DMDD) programme, cataloguing the morphological defects identified from comprehensive imaging of 220 homozygous mutant and 114 wild type embryos from 42 lethal and subviable lines, analysed at E14.5. Results: Virtually all mutant embryos show multiple abnormal phenotypes and amongst the 42 lines these affect most organ systems. Within each mutant line, the phenotypes of individual embryos form distinct but overlapping sets. Subcutaneous edema, malformations of the heart or great vessels, abnormalities in forebrain morphology and the musculature of the eyes are all prevalent phenotypes, as is loss or abnormal size of the hypoglossal nerve. Conclusions: Overall, the most striking finding is that no matter how profound the malformation, each phenotype shows highly variable penetrance within a mutant line. These findings have challenging implications for efforts to identify human disease correlates.